Establishment of the MGH Postpartum Psychosis Project: MGHP3 - Lee S. Cohen; Rachel Vanderkruik; Miranda Arakelian; Taylor R. Church; Madison M. Dunk; Marlene P. Freeman (PLoS ONE, 2023)
Objective Postpartum psychosis (PP) is a severe psychiatric disorder, with incomplete consensus on definition and diagnostic criteria. The Massachusetts General Hospital Postpartum Psychosis Project (MGHP3) was established to better ascertain the phenomenology of PP in a large cohort of diverse women spanning a wide geographical range (primarily in the US), including time of onset, symptom patterns, and associated comorbidities, psychiatric diagnoses pre- and post- the episode of PP, and also to identify genomic and clinical predictors of PP. This report describes the methods of MGHP3 and provides a status update. Method Data are collected from women who experienced PP within 6 months of childbirth and who provided this information within ten years of the study interview. Subject data are gathered during a one-time structured clinical interview conducted by phone, which includes administration of the Mini International Neuropsychiatric Interview for Psychotic Disorders Studies (Version 7.0.2), the MGHP3© Questionnaire, and other information including lifetime mental health history and use of psychiatric medications both prior to the episode of PP and during the subsequent time period prior to study interview. Subjects also provide a saliva sample to be processed for genomic analyses; a neuroimaging assessment is also conducted for a subset of participants. Results As of July 1, 2022, 311 subjects from 44 states and 7 countries were enrolled in MGHP3. Recruitment sources include social media, online advertisements, physician referral, community outreach, and partnership with PP advocacy groups. Conclusions The rigorous phenotyping, genetic sampling, and neuroimaging studies in this sample of women with histories of PP will contribute to better understanding of this serious illness. Findings from MGHP3 can catalyze ongoing discussions in the field regarding proper nosologic classification of PP as well as relevant treatment implications.